Defect-free Ni/GaN Schottky barrier behavior with high temperature stability - Reddy, Pramod; Sarkar, Biplab; Kaess, Felix; Gerhold, Michael; Kohn, Erhard; Collazo, Ramon; Sitar, Zlatko (Applied physics letters, 2017)
In this work, we report on defect-free homogeneous behavior of Ni Schottky contacts patterned on surface treated n-GaN by photolithography with unity ideality factor, high temperature stability, and low reverse leakage. The barrier height (0.7 eV) and ideality factor (1.02) are found to be independent of temperature, indicating a highly homogeneous contact. The contacts are found to be stable with no significant change in ideality factor or leakage current up to an annealing temperature of 600 °C. Temperature dependence of the reverse leakage current shows no evidence for the existence of surface defects that would provide leakage paths, and the behavior was modeled by ATLAS simulations with an ideal homogeneous barrier of 0.7 eV. Consequently, the forward and reverse bias characteristics are explained by a common set of parameters. The surface treatment after the development and prior to metallization included an acid-based surface treatment. X-ray photoelectron spectroscopy (XPS) studies indicate that the hydroxide-based development process during photolithography changes the nitride surface composition by introducing excess C that degrades the ideality factor and introduces barrier inhomogeneity and high leakage currents. XPS studies further demonstrate that the restoration of a stable, Ga-rich surface, similar to as-grown surface, occurs due to the acid-based surface treatment, which is responsible for the observed unity ideality factor, homogeneous barrier, low leakage current, and high temperature stability.